Effects of digital transformation on information activities and competencies - Moreiro-González, José-Antonio (Anuario ThinkEPI, 2022)
This paper assesses the significance achieved by digital transformation, especially concerning the information sector during the Covid-19 pandemic. Once the concept of digital transformation and its attributes have been established, the paper addresses policy and business initiatives that support this transformation and the prevention of the digital divide. Transversal digital competences are then considered as a key enabler when it comes to e-learning and teleworking in university education, and their repercussions when it comes to enabling e-learning and teleworking are also discussed.
Keywords: Transformación digital; Competencias digitales; Transversalidad; Teletrabajo; Formación virtual; Profesionales de la información